(untitled) (Intent Research Scientific Journal, 2023)
In the manufacture of removable prostheses, the problem of design features often arises, the choice of the fixation method. Fixation systems with wire clamps are outdated, but outdated, but are widely used in clinical practice. In addition to the fact that such prostheses are unaesthetic, such prostheses are not only unaesthetic, but also increase the atrophy of the tissues of the basis of the prosthesis, which ultimately leads to a deterioration in the fixation of the prosthesis.which leads to a deterioration in the fixation of the prosthesis (Kalinina N.V., Markov B.P.). Currently, a number of improved prosthesis designs have been proposed.A number of more advanced orthopedic structures are proposed that allow using the remaining teeth as supports for removable prostheses (Kalinina N.V., Markov B.P.).As abutments for fixing removable dentures. One of these designs is a removable prosthesis with a telescopic fixation system.The telescopic fixation system is represented by a metal crown with a 6° cone in the non-removable part. The removable part with a 6° cone is a plastic base on which an artificial tooth is attached